Diversity of aerobic spore-forming bacteria isolated from fresh bee pollen intended for human consumption - Alippi, Adriana Mónica (2021)
Bee pollen is the result of the agglutination of pollen grains collected from flowers and mixed with nectar and salivary secretions by honey bees. Bee pollen is a natural product exposed to environmental conditions and also provides a unique microhabitat for yeasts and bacterial com munities. We analyzed 30 fresh bee pollen samples obtained from the main producing areas of Argentina to identify aerobic-spore-forming bacteria. We obtained 73 isolates belonging to 16 different species through isolation on selective and differential media, morphological and bio chemical tests, and PCR and RFLP analysis of genes encoding 16S rRNA. Our data revealed that Bacillus cereus sensu stricto was the most predominant species (50%), followed by Bacillus mega terium (40%) and Bacillus subtilis (40%), respectively. In a minor proportion, Paenibacillus poly myxa (20%), Paenibacillus larvae (17%), Bacillus pumilus (13%), Bacillus licheniformis (13%), Bacillus amyloliquefaciens (10%), Lysinibacillus sphaericus (7%), Bacillus coagulans (7%), Rummelliibacillus stabekisii (7%), Bacillus thuringiensis (7%), Bacillus clausii (3%), Paenibacillus alvei (3%), Bacillus simplex (3%), and Paenibacillus amylolyticus (3%) were also found. Our results showed that Argentinean bee pollen could transmit honey bee diseases due to the presence of viable spores of P. larvae and also spores of toxicogenic B. cereus s.s. and B. megaterium strains.